Analysis of the Benefits of Infrastructure Development in Lakatan Village, Galang Sub District Tolitoli District in Year 2017 - 2019 - Ramlawati; Hilmi (Dwijendra University, 2020)
The purpose of this study was to determine the benefits of infrastructure development in Lakatan village, Galang sub district Tolitoli district, which is sourced from village funds from 2017-2019. This study uses a qualitative descriptive approach to the type of data reduction research. This research was conducted to look at the benefits of infrastructure development in terms of economic, education, health and sosial cultural benefits for village in Lakatan. Data obtained from interviews, observations and documentation. The data is analyzed means of preparation and processing of data and drawing conclusions. The results of this study show : the benefits of infrastructure development are very beneficial to improve the economy of rural communities.